Pasien Perempuan 45 Tahun dengan Ulkus Kornea Cum Hipopion Okuli Dekstra : Sebuah Laporan Kasus - Aulia Ghina Sabilla; Muhammad Maulana (CV. Jasa Sukses Abadi, 2026)
The cornea is a transparent, avascular layer located at the front of the eye, primarily functioning to protect the eyeball. It consists of five distinct layers: the epithelium, Bowman's membrane, stroma, Descemet's membrane, and endothelium. The corneal epithelium plays a crucial role as a barrier against infection. Damage to the epithelial layer allows external substances to penetrate the underlying tissues, potentially leading to a corneal ulcer. A corneal ulcer is a pathological condition characterized by a lesion or defect in the corneal epithelium, resulting from a loss of tissue integrity and accompanied by an inflammatory infiltrate. This condition can affect the cornea from the epithelium to the stroma and constitutes an ophthalmic emergency that can severely threaten vision. Corneal ulcers are frequently associated with hypopyon, which is an inflammatory reaction in the anterior chamber of the eye, visible as a white layer that settles at the bottom of the chamber due to gravity. In this case report, a 45-year-old woman presented with a red right eye and decreased visual acuity that had persisted for one month. The patient reported a history of ocular trauma from being struck by grass while pulling weeds. Ophthalmological examination revealed a visual acuity of 1/300 in the right eye (OD), bulbar conjunctival injection, hyperemia of the fornix and palpebral conjunctiva, positive ciliary injection, a cloudy cornea with a distinct, excavated central lesion measuring 9 mm x 7 mm, and hypopyon occupying the lower one-third (1/3) of the anterior chamber. Visual acuity in the left eye (OS) was 6/6, and the anterior segment of the OS was within normal limits. The management provided included medicamentous therapy, non-medicamentous therapy, and a plan for operative intervention. The medicamentous regimen for the right eye consisted of topical Moxifloxacin 0.5% hourly, Natamycin 5% every 3 hours, Atropine Sulfate 1% every 8 hours, Sodium Potassium Chloride every 4 hours, and systemic therapy with Ciprofloxacin tablets 2x500 mg and Ketoconazole tablets 3x200 mg.